Cyclic Electron Flow around Photosystem I in C(3) Plants. In Vivo Control by the Redox State of Chloroplasts and Involvement of the NADH-Dehydrogenase Complex - Joët, Thierry (American Society of Plant Biologists, 2002)
Cyclic electron flow around photosystem (PS) I has been widely described in vitro in chloroplasts or thylakoids isolated from C(3) plant leaves, but its occurrence in vivo is still a matter of debate. Photoacoustic spectroscopy and kinetic spectrophotometry were used to analyze cyclic PS I activity in tobacco (Nicotiana tabacum cv Petit Havana) leaf discs illuminated with far-red light. Only a very weak activity was measured in air with both techniques. When leaf discs were placed in anaerobiosis, a high and rapid cyclic PS I activity was measured. The maximal energy storage in far-red light increased to 30% to 50%, and the half-time of the P(700) re-reduction in the dark decreased to around 400 ms; these values are comparable with those measured in cyanobacteria and C(4) plant leaves in aerobiosis. The stimulatory effect of anaerobiosis was mimicked by infiltrating leaves with inhibitors of mitochondrial respiration or of the chlororespiratory oxidase, therefore, showing that changes in the redox state of intersystem electron carriers tightly control the rate of PS I-driven cyclic electron flow in vivo. Measurements of energy storage at different modulation frequencies of far-red light showed that anaerobiosis-induced cyclic PS I activity in leaves of a tobacco mutant deficient in the plastid Ndh complex was kinetically different from that of the wild type, the cycle being slower in the former leaves. We conclude that the Ndh complex is required for rapid electron cycling around PS I.